Cadmium sulfide photocatalyst based on gradient concentration cadmium vacancy induced ordered phase polarization electric field, and preparation method and application thereof

CN122875253APending Publication Date: 2026-10-09TIANFU JIANGXI LAB
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202610842534.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]针对现有技术所存在的上述缺点,本发明提供了基于梯度浓度镉空位诱导有序体相极化电场的硫化镉光催化剂及制备方法,能够有效解决现有技术光催化中传统异质结界面内建电场作用范围有限、强度较弱,无法抑制体相电荷复合的问题

Benefits of technology

[0029]1、本发明通过在非中心对称六方晶系硫化镉中构建梯度浓度Cd空位并采用两步程序化退火工艺,在硫化镉体相内诱导形成贯穿整个材料的有序极化电场,克服了传统异质结内建电场仅局限于界面空间电荷区、作用范围有限、强度较弱的固有缺陷,从根本上驱动光生电子-空穴对在体相内的高效分离与定向传输,在不负载任何贵金属助催化剂的条件下实现了400 mmol·h-1·g-1的光催化产氢速率,超越现有技术中的硫化镉基光催化剂性能;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875253A_ABST
    Figure CN122875253A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of photocatalytic materials, in particular to a cadmium sulfide photocatalyst based on a gradient concentration cadmium vacancy induced ordered phase polarization electric field, a preparation method and application; a mixed solution of a cadmium source and a sulfur source is prepared into a cadmium sulfide nanosheet precursor through a hydrothermal method under alkaline conditions; the cadmium sulfide nanosheet precursor is heat-treated under a sulfur-containing inert gas atmosphere, and then first constant-temperature annealing is carried out; then second constant-temperature annealing is carried out under an inert gas atmosphere, and the annealing temperature is the same as that of the first constant-temperature annealing; finally, two-stage cooling treatment is carried out under an inert gas atmosphere, and a cadmium sulfide nanosheet material with a gradient concentration Cd vacancy is obtained; a high-intensity ordered polarization electric field is constructed, can effectively resist the coulomb attraction, promote the separation and transmission of the bulk phase photo-generated electrons and holes, and realizes the effects of high hydrogen production activity, high stability and cycle of water photocatalytic decomposition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalytic materials technology, specifically to cadmium sulfide photocatalysts based on gradient concentration cadmium vacancy-induced ordered bulk phase polarized electric fields, their preparation methods, and applications. Background Technology

[0002] With increasingly severe energy and environmental problems, the development of clean and renewable energy sources is urgently needed. Hydrogen, due to its abundant sources, high calorific value, lack of pollution, and storability, is considered a highly promising clean fuel. In 1972, scientists discovered that using semiconductor materials as catalysts could achieve solar-powered photocatalytic water splitting to produce hydrogen. This method uses only sunlight and water as raw materials, making it a clean and sustainable hydrogen production route. Semiconductor photocatalysts are the core medium for converting solar energy into chemical energy. Cadmium sulfide (CdS), due to its suitable band structure and conduction band potential (Eg = 2.40 V, CB = −0.52 V, VB = 1.88 V), can effectively absorb visible light and possesses sufficient reduction driving force, making it considered one of the most promising photocatalytic semiconductor materials.

[0003] However, due to Coulomb forces, electron-hole pairs generated by photoexcitation in CdS readily recombine before reaching the active sites on the surface, severely limiting photocatalytic efficiency. To promote the separation and transport of electron-hole pairs, existing technologies typically employ a strategy of constructing heterojunctions to create a built-in electric field at the interface. For example, Chinese patent CN116809090A discloses a 2D / 1DNi2P / CdS heterojunction catalyst, in which the Ni2P loading improves the photoresponse range and intensity of CdS, reduces the electron-hole recombination rate, and achieves a hydrogen production rate of 4.3 mmol / h / g; Chinese patent CN115445637B discloses a Cd / CdS heterojunction, with a photocatalytic water splitting hydrogen production efficiency of 10.6 mmol / h / g; Chinese patent CN119140123A discloses an indirect / direct heterojunction type MoS2 / CdS composite photocatalytic material, which inhibits the recombination of photogenerated carriers and optimizes the band structure, achieving a photocatalytic hydrogen production rate of 9.7 mmol / h / g; and Chinese patent CN121130914A discloses a NiO·NiS / CdS ternary composite heterojunction photocatalyst, which effectively promotes the separation and migration of photogenerated carriers, achieving a hydrogen production rate of 32 mmol / h / g. While the aforementioned heterojunction strategies have promoted electron-hole pair separation to some extent, they generally suffer from the following shortcomings: First, most photogenerated electron-hole recombination occurs deep within the bulk phase of the semiconductor catalyst, while the built-in electric field formed by the heterojunction exists only in the space charge region near the interface, with a limited range of influence (typically only on the order of nanometers to tens of nanometers). Its driving effect on photogenerated carriers generated in the bulk region far from the interface is weak, and it cannot effectively suppress bulk charge recombination. Second, the effectiveness of the built-in electric field is highly dependent on the atomic-level contact quality of the heterojunction interface. Defects, dangling bonds, or impurities at the interface can become charge recombination centers, severely weakening or even negating the separation effect of the electric field. Third, constructing heterojunctions typically involves complex control requirements such as band matching and lattice adaptation of two or more materials, making synthesis difficult. Furthermore, additional defects and resistance introduced at the interface may bring new carrier recombination pathways, making it difficult to balance separation efficiency and transport rate.

[0004] Therefore, how to overcome the fundamental bottleneck of the limited range and weak intensity of the built-in electric field at the interface of traditional heterojunctions, and construct a new electric field mechanism that can penetrate the entire catalyst bulk phase and drive the efficient separation and directional transport of photogenerated carriers from the inside, while maintaining the intrinsic stability of the material, is a key technical problem that urgently needs to be solved in the field of photocatalytic water splitting for hydrogen production. Summary of the Invention

[0005] To address the aforementioned shortcomings of existing technologies, this invention provides a cadmium sulfide photocatalyst and its preparation method based on an ordered bulk polarized electric field induced by gradient concentration cadmium vacancies. This effectively solves the problem that the built-in electric field at the interface of traditional heterojunctions in existing photocatalysis technologies has a limited range and weak intensity, making it unable to suppress bulk charge recombination.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] In a first aspect, the present invention provides a method for preparing a cadmium sulfide photocatalyst based on an ordered bulk polarization electric field induced by gradient concentration cadmium vacancies, the method comprising:

[0008] (1) Cadmium sulfide nanosheet precursor was prepared by hydrothermal method under alkaline conditions from a mixture of cadmium source and sulfur source;

[0009] (2) The cadmium sulfide nanosheet precursor is heat-treated in a sulfur-containing inert gas atmosphere and then subjected to a first isothermal annealing to generate a high concentration of Cd vacancies on the surface layer of the cadmium sulfide nanosheet.

[0010] (3) The product obtained after step (2) is subjected to a second isothermal annealing in an inert gas atmosphere, and the annealing temperature is the same as the temperature of the first isothermal annealing.

[0011] (4) Under an inert gas atmosphere, the product after step (3) is subjected to a two-stage cooling process to obtain cadmium sulfide nanosheet material with gradient concentration of Cd vacancies.

[0012] Furthermore, in step (1), the preparation of cadmium sulfide nanosheet precursors from a mixture of cadmium and sulfur sources under alkaline conditions via a hydrothermal method includes:

[0013] The cadmium source and sulfur source were dissolved separately in deionized water to prepare solutions. The two solutions were then mixed, and an alkaline reagent was added under stirring to adjust the pH of the solution to 9-11, thus forming a mixed solution.

[0014] The mixed solution was transferred to a high-pressure reactor and sealed, and reacted at a constant temperature of 120–180°C for 10–20 h.

[0015] After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The precipitate was then washed, centrifuged, and collected. It was then vacuum dried at 50–80 °C for 2–10 h to obtain the cadmium sulfide nanosheet precursor.

[0016] Furthermore, in step (2), before heat-treating the cadmium sulfide nanosheet precursor, an inert gas is introduced into the reaction system at a flow rate of 50–150 sccm for 10–60 min to remove air from the system.

[0017] Furthermore, in step (2), the sulfur-containing inert gas atmosphere is obtained by placing a solid sulfur source upstream of the inert carrier gas flow and heating it to 100-300°C to generate sulfur vapor, which is then transported with the inert carrier gas to the reaction temperature zone where the cadmium sulfide nanosheet precursor is located.

[0018] Furthermore, in step (2), the heating rate of the heat treatment is 2 to 8 °C / min.

[0019] Furthermore, in step (2), the temperature of the first isothermal annealing is 300-600℃, and the annealing time is 30-120 min.

[0020] Furthermore, in step (3), the temperature of the second isothermal annealing is 300-600℃, and the annealing time is 30-90 min.

[0021] Furthermore, in step (4), the two-stage cooling process includes:

[0022] First, a slow cooling process controlled by a program is performed to lower the temperature to 100-300℃, and then a second rapid cooling process is performed to lower the temperature to room temperature.

[0023] The cooling rate of the first stage of slow cooling is 1–5 °C / min.

[0024] Furthermore, the cadmium source is one of cadmium acetate, cadmium nitrate, cadmium chloride, cadmium perchlorate, cadmium carbonate, cadmium chloride, cadmium bromide, and cadmium iodide, and the sulfur source is one of thiourea, sodium sulfide, thioacetamide, sodium thiosulfate, ammonium sulfide, and ammonium thiosulfate.

[0025] The alkaline reagent is one of ammonia, ethylenediamine, ethanolamine, triethanolamine, sodium hydroxide, and potassium hydroxide.

[0026] In a second aspect, the present invention also provides a cadmium sulfide photocatalyst based on an ordered bulk phase polarization electric field induced by gradient concentration cadmium vacancies, prepared according to the preparation method described in the first aspect, wherein the concentration of Cd vacancies in the cadmium sulfide catalyst exhibits a gradient distribution that decreases from the surface to the interior.

[0027] Thirdly, the present invention also provides the application of cadmium sulfide photocatalysts based on gradient concentration cadmium vacancy-induced ordered bulk phase polarization electric fields in photocatalytic water splitting for hydrogen production.

[0028] The technical solution provided by this invention has the following advantages compared with the known prior art:

[0029] 1. This invention constructs a gradient concentration of Cd vacancies in non-centrosymmetric hexagonal cadmium sulfide and employs a two-step programmed annealing process to induce an ordered polarized electric field throughout the entire cadmium sulfide bulk phase. This overcomes the inherent defects of traditional heterojunctions, where the built-in electric field is limited to the interfacial space charge region, has a limited range of action, and is relatively weak. It fundamentally drives the efficient separation and directional transport of photogenerated electron-hole pairs within the bulk phase, achieving a concentration of 400 mmol·h⁻¹ without loading any noble metal co-catalysts. -1 ·g -1 The photocatalytic hydrogen production rate surpasses the performance of existing cadmium sulfide-based photocatalysts;

[0030] 2. This invention achieves gradient vacancy construction through atmosphere switching. In the first stage, high-temperature annealing is carried out in a sulfur-containing atmosphere. The high chemical potential of S vapor suppresses the formation of S vacancies, while simultaneously promoting the selective escape of Cd atoms from the lattice, precisely generating a high concentration of Cd vacancies on the surface layer of cadmium sulfide nanosheets. In the second stage, the atmosphere is switched to a pure inert gas (such as Ar) to remove the S vapor source. At this time, the high concentration of Cd vacancies enriched on the surface spontaneously diffuses into the lower concentration bulk phase under the driving force of high temperature, thereby forming a concentration gradient from the surface to the interior. This achieves directional control over the vacancy type and generation region, solving the problem that conventional doping methods can only introduce randomly distributed defects on the material surface.

[0031] 3. This invention precisely separates the two kinetic processes of vacancy surface generation and bulk diffusion in time and space by switching the annealing atmosphere (sulfur-containing atmosphere → pure inert atmosphere) and combining it with inert gas purging. This achieves a step-by-step construction of surface enrichment followed by bulk diffusion, allowing the high concentration of Cd vacancies enriched on the surface to spontaneously diffuse into the bulk phase under the drive of the concentration gradient, forming a Cd vacancy gradient distribution with a continuously decreasing concentration from the surface to the interior. This solves the problem that conventional methods can only form randomly distributed defects on the material surface. This gradient structure breaks the original charge balance of the crystal, inducing a uniformly oriented dipole moment, thereby forming a macroscopically ordered polarized electric field that permeates the entire crystal bulk phase. Its intensity is far higher than the diffusion electric field caused by the concentration difference and the built-in electric field at the heterojunction interface. This solves the problem that disordered defects easily form strong recombination centers, trapping and annihilating photogenerated carriers. Furthermore, the directional polarized electric field drives photogenerated electrons and holes to migrate to specific crystal planes, fundamentally solving the problem of S induced by holes. 2- Oxidation (photocorrosion) process improves the intrinsic stability of materials;

[0032] 4. This invention utilizes the high-temperature vacancy diffusion kinetics to drive the migration of surface-enriched Cd vacancies into the bulk phase by performing a second isothermal annealing at the same temperature as the first step under a pure inert atmosphere. This achieves the depth expansion and concentration control of the vacancy gradient without destroying the crystal structure, making the intensity and penetration depth of the polarization electric field adjustable. This provides a directional driving force for photogenerated charge carriers to penetrate the entire catalyst bulk phase, effectively overcoming the Coulomb attraction of electron-hole pairs and greatly suppressing bulk recombination.

[0033] 5. The present invention employs a two-stage cooling process: first, the temperature is slowly reduced to 100-300°C at a rate of 1-5°C / min, and then rapidly cooled to room temperature. During the slow cooling stage, the thermodynamic equilibrium vacancy gradient structure formed at high temperature is gradually "frozen" and locked, preventing rapid cooling from causing the vacancy to re-homogenize and ensuring the precise preservation of the gradient vacancy distribution in the final product.

[0034] 6. This invention uses cadmium sulfide nanosheets synthesized by hydrothermal method as a precursor. The high specific surface area of ​​its two-dimensional thin sheet structure enables full contact between the annealing atmosphere and the material surface. At the same time, the nanosheet structure significantly shortens the path length of vacancies diffuse from the surface to the bulk phase, which is conducive to the efficient construction and precise control of gradient vacancies and ensures the penetration of the polarization electric field within a limited thickness. Attached Figure Description

[0035] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0036] Figure 1 The CdS nanosheet precursor and gradient-V of this invention Cd A schematic diagram of the preparation technology route for / CdS;

[0037] Figure 2 For the present invention, gradient-V Cd XRD spectrum of / CdS;

[0038] Figure 3 The present invention uses CdS and gradient-V Cd SEM image of / CdS;

[0039] Figure 4 The present invention uses CdS and gradient-V Cd UV-Vis absorption spectrum of / CdS;

[0040] Figure 5The present invention uses CdS and gradient-V Cd Time-resolved fluorescence spectrum of CdS (TRPL);

[0041] Figure 6 The present invention is based on CdS and surface disordered V. Cd / CdS and gradient-V Cd Comparison of hydrogen production performance of / CdS. Detailed Implementation

[0042] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.

[0043] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail. The terms “comprising,” “including,” “having,” “containing,” etc., as used herein are open-ended terms, meaning that they include but are not limited to. Unless the context clearly indicates otherwise, the expressions “a” and “an” as used herein include plural references. It should be noted that “first,” “second,” etc., are used merely for convenience of description and distinction and should not be construed as indicating or implying relative importance. The term “about” as used herein indicates a range of ±20% of the following numerical value. In some embodiments, the term “about” indicates a range of ±10% of the following numerical value. In some embodiments, the term “about” indicates a range of ±5% of the following numerical value. The invention is further described below with reference to embodiments.

[0044] To address the challenges of limited range and weak intensity of the built-in electric field at the interface of traditional heterojunctions in photocatalysis, which fails to suppress bulk charge recombination, and to overcome the limitations of conventional doping methods that only introduce disordered defects on the material surface and cannot effectively control bulk charge behavior, this invention provides a CdS photocatalyst based on an ordered bulk polarization electric field induced by gradient concentration cadmium vacancies, abbreviated as gradient-V. Cd / CdS photocatalyst, V CdRepresenting Cd vacancies, a strategy is employed to introduce gradient concentrations of Cd vacancies into non-centrosymmetric hexagonal CdS crystals via programmed thermal annealing, thereby constructing an ordered polarization electric field with tunable intensity that permeates the entire bulk phase of the material. This strategy not only constructs a polarization electric field with high intensity that can act on the bulk phase of the catalyst (10... 8 (V / m) to compensate for the shortcomings of the built-in electric field in traditional heterojunctions, and by constructing a gradient concentration vacancy-induced gradient bulk polarization electric field, it fundamentally drives the efficient bulk separation and directional transport of photogenerated carriers. For example... Figure 1 The diagram shows a schematic of the preparation technology route. The specific preparation method includes the following steps:

[0045] 1. Dissolve 2-4 mmol of Cd(CH3COO)2·2H2O and 2-4 mmol of CS(NH2)2 in 20-50 mL of deionized water respectively;

[0046] 2. Mix the two solutions, and add NH3·H2O dropwise under magnetic stirring to adjust the pH of the solution to 9-11;

[0047] 3. Transfer the mixed solution to a 100 mL polytetrafluoroethylene-lined high-pressure reactor, seal it, and place the reactor in an oven to react at a constant temperature of 120~180℃ for 10~20 h.

[0048] 4. After the reaction is complete, allow the mixture to cool naturally to room temperature. Wash the mixture with deionized water and ethanol alternately 1 to 5 times. Centrifuge to collect the yellow precipitate and dry it in a vacuum drying oven at 50 to 80°C for 2 to 10 hours to obtain the stoichiometric CdS nanosheet precursor.

[0049] 5. Weigh approximately 50-150 mg of the above CdS precursor powder and evenly spread it in a quartz boat. Place the quartz boat in the main heating zone (zone I) of the tube furnace. Place another quartz boat containing high-purity sulfur powder in another zone (zone II) upstream of the gas flow as a sulfur vapor source.

[0050] 6. Seal the quartz tube, open the inlet and outlet valves, and introduce high-purity Ar gas at a flow rate of 50~150 sccm for 10~60 minutes to remove air from the tube.

[0051] 7. Heat the sulfur source temperature zone (temperature zone II) to 100~300℃ to generate stable sulfur vapor. The S vapor atmosphere inhibits the formation of S vacancies and promotes the escape of Cd atoms from the crystal lattice at high temperatures, thereby forming Cd vacancies. Simultaneously, program the temperature of the main temperature zone (temperature zone I) to 300~600℃ at a rate of 2~8℃ / min, and perform a first isothermal annealing in this sulfur vapor / argon mixed atmosphere for 30~120 min; (during this stage, S atoms diffuse into the CdS crystal, while Cd atoms escape from the crystal lattice, forming Cd vacancies (V... Cd This step aims to generate a high concentration of Cd vacancies on the sample surface layer.

[0052] 8. After the first isothermal annealing is completed, turn off the heating of the sulfur source temperature zone and maintain the argon flow rate to purge the reaction tube for 5~30 minutes to completely remove the residual sulfur vapor in the tube.

[0053] 9. Under a pure argon atmosphere, maintain the temperature of the main temperature zone of the sample at 300~600℃ and continue the second isothermal annealing for 30~90 min. During this stage, the Cd vacancies enriched on the surface diffuse into the bulk phase of the material driven by the concentration gradient, thus forming a vacancy distribution gradient with decreasing concentration from the surface to the interior;

[0054] 10. After the second isothermal annealing, turn off the heating power. Under continuous argon protection, perform a two-stage cooling process. The first stage involves slowly cooling the furnace body to 100-300°C at a set rate of 1-5°C / min. This process fixes the formed vacancy gradient structure. The second stage involves opening the furnace door to rapidly cool it to room temperature, thus obtaining CdS nanosheet material gradient-V with a gradient concentration of Cd vacancies. Cd / CdS.

[0055] In the above preparation process, a polarized electric field is constructed in the bulk CdS phase of the non-centrosymmetric hexagonal crystal system by introducing vacancy defects. This solves the problem that the built-in electric field of existing heterojunctions can only act on the material surface and has a weak strength, fundamentally solving the problem of severe carrier recombination in the bulk phase of semiconductor photocatalysts, rather than simply optimizing surface carrier separation. Controllable gradient concentration vacancies are constructed inside CdS through programmed annealing and atmosphere control, solving the problem that conventional methods can only form randomly distributed defects on the material surface. The constructed gradient concentration ordered defects can induce dipole moments with consistent directions, thereby forming a macroscopically ordered polarized electric field. This solves the problem that disordered defects form strong recombination centers, capturing and annihilating photogenerated carriers, leading to low charge separation efficiency. The time-atmosphere programmed control method is employed. The annealing process is divided into two continuous stages with drastically different atmospheric conditions. By precisely controlling the competition and synergy between the two kinetic processes of surface reaction and bulk diffusion, the vacancy gradient can be controllably constructed. The gradient vacancy is constructed by switching atmospheres. The first stage is a sulfur-rich atmosphere: annealing is carried out in the presence of sulfur vapor. The high chemical potential of sulfur strongly suppresses the loss of sulfur atoms on the material surface, while promoting the escape of Cd atoms from the lattice. This stage aims to selectively introduce a high concentration of Cd vacancies into the outermost layer of the material. The second stage is an inert atmosphere: switching to a pure inert gas (such as Ar) atmosphere and removing the sulfur vapor source. At this time, the high concentration of Cd vacancies enriched on the surface spontaneously diffuses into the lower concentration bulk phase under the drive of high temperature, thus naturally forming a concentration gradient from the surface to the interior.

[0056] The precursor of this invention has a specific morphology. CdS nanosheets synthesized via a hydrothermal method are used as the precursor. Their two-dimensional sheet structure has a high specific surface area, which is beneficial for the full interaction between the atmosphere and the surface. Furthermore, the short diffusion path facilitates the efficient formation and control of the gradient. This invention uses a dual-temperature zone tube furnace, specifically placing the CdS precursor powder sample in the main temperature zone and the solid S source in an independent, upstream low-temperature zone as a sulfur vapor source. This spatial separation layout is a prerequisite for achieving controllable S vapor partial pressure and precise atmosphere switching. In addition, this invention controls the sulfur source temperature at 100-200℃ (preferably 150℃) to generate a suitable amount of stable S vapor, suppressing S vacancy formation without over-sulfiding the surface. The sample annealing temperature and time are maintained at 400-500℃ (preferably 480℃) for 30-120 min (preferably 30 min) to ensure sufficient Cd escape from the surface, forming a high-concentration vacancy layer.

[0057] This invention employs atmosphere switching and purging. After shutting off the sulfur source heating, the system is purged with inert gas. This operation aims to thoroughly remove residual sulfur vapor in the reaction chamber and ensure that the second stage is carried out in a pure inert atmosphere. This is a necessary guarantee for achieving atmosphere differentiation between the two steps.

[0058] This invention involves a second isothermal annealing at the same high temperature under a pure inert atmosphere. This stage is crucial for the formation of vacancy gradient diffusion. After annealing, the temperature is slowly lowered to below a certain critical temperature using a controlled cooling rate, followed by rapid cooling. This gradient freezing step is essential for locking the vacancy gradient distribution formed at high temperature and preventing it from becoming homogenized due to rapid cooling. The sulfur vapor atmosphere of this invention inhibits the formation of sulfur vacancies and promotes the escape of Cd atoms from the crystal lattice at high temperatures, thereby forming Cd vacancies. The main temperature zone (temperature zone I) is heated and isothermal annealed in this sulfur vapor / argon mixed atmosphere. During this stage, sulfur atoms diffuse into the interior of the CdS crystal, while Cd atoms escape from the crystal lattice, forming Cd vacancies (V). Cd The aim is to generate a high concentration of Cd vacancies on the sample surface layer.

[0059] Example: Refer to Figures 1 to 6 .

[0060] Example 1

[0061] A gradient-V method for constructing an ordered bulk phase polarization electric field induced by gradient concentration vacancies Cd / CdS photocatalyst preparation method:

[0062] 1. Dissolve 2 mmol of Cd(CH3COO)2·2H2O and 2 mmol of CS(NH2)2 in 20 mL of deionized water respectively;

[0063] 2. Mix the two solutions, and add NH3·H2O dropwise under magnetic stirring to adjust the pH of the solution to 9;

[0064] 3. Transfer the mixed solution to a 100 mL polytetrafluoroethylene-lined high-pressure reactor, seal it, and place the reactor in an oven to react at a constant temperature of 120°C for 12 h.

[0065] 4. After the reaction is complete, the mixture is allowed to cool naturally to room temperature. It is then washed once with deionized water and ethanol alternately. The yellow precipitate is collected by centrifugation and dried in a vacuum drying oven at 50°C for 2 h to obtain the stoichiometric CdS nanosheet precursor.

[0066] 5. Weigh about 50 mg of the above CdS precursor powder and spread it evenly in a quartz boat. Place the quartz boat in the main heating zone (zone I) of the tube furnace. Place another quartz boat containing high-purity sulfur powder in another zone (zone II) upstream of the gas flow as a sulfur vapor source.

[0067] 6. Seal the quartz tube, open the inlet and outlet valves, and introduce high-purity Ar gas at a flow rate of 50 sccm for 10 minutes to remove air from the tube.

[0068] 7. Heat the sulfur source temperature zone (temperature zone II) to 100℃ to generate stable sulfur vapor. At the same time, program the temperature of the main temperature zone (temperature zone I) to 300℃ at a rate of 2℃ / min, and anneal at this temperature for 30 min under the sulfur vapor / argon mixed atmosphere.

[0069] 8. After the first annealing is completed, turn off the heating of the sulfur source temperature zone and maintain the argon flow rate to purge the reaction tube for 5 minutes to completely remove the residual sulfur vapor in the tube;

[0070] 9. Under a pure argon atmosphere, maintain the temperature of the main temperature zone of the sample at 300℃ and continue the isothermal annealing for 30 min.

[0071] 10. After the second annealing, turn off the heating power. Under continuous argon protection, slowly cool the furnace to 100°C at a set rate of 1°C / min. This process fixes the formed vacancy gradient structure. Then open the furnace door to allow it to cool rapidly to room temperature, thus obtaining CdS nanosheet material gradient-V with a gradient concentration of Cd vacancies. Cd / CdS.

[0072] Example 2

[0073] A gradient-V method for constructing an ordered bulk phase polarization electric field induced by gradient concentration vacancies Cd / CdS photocatalyst preparation method:

[0074] 1. Dissolve 2 mmol of Cd(CH3COO)2·2H2O and 4 mmol of CS(NH2)2 in 20 mL of deionized water respectively;

[0075] 2. Mix the two solutions and add NH3·H2O dropwise under magnetic stirring to adjust the pH of the solution to 10;

[0076] 3. Transfer the mixed solution to a 100 mL polytetrafluoroethylene-lined high-pressure reactor, seal it, and place the reactor in an oven to react at 160°C for 12 h.

[0077] 4. After the reaction is complete, the mixture is allowed to cool naturally to room temperature. It is then washed three times with deionized water and ethanol, centrifuged to collect the yellow precipitate, and dried in a vacuum drying oven at 50°C for 6 h to obtain the stoichiometric CdS nanosheet precursor.

[0078] 5. Weigh approximately 100 mg of the above CdS precursor powder and evenly spread it in a quartz boat. Place the quartz boat in the main heating zone (zone I) of the tube furnace. Place another quartz boat containing high-purity sulfur powder in another zone (zone II) upstream of the gas flow as a sulfur vapor source.

[0079] 6. Seal the quartz tube, open the inlet and outlet valves, and introduce high-purity Ar gas at a flow rate of 50 sccm for 30 minutes to remove air from the tube.

[0080] 7. Heat the sulfur source temperature zone (temperature zone II) to 300℃ to generate stable sulfur vapor. At the same time, program the temperature of the main temperature zone (temperature zone I) to 300℃ at a rate of 5℃ / min, and anneal at a constant temperature for 30 min in the sulfur vapor / argon mixed atmosphere.

[0081] 8. After the first annealing is completed, turn off the heating of the sulfur source temperature zone and maintain the argon flow rate to purge the reaction tube for 10 minutes to completely remove the residual sulfur vapor in the tube;

[0082] 9. Under a pure argon atmosphere, maintain the temperature of the main temperature zone of the sample at 300℃ and continue the isothermal annealing for 60 min.

[0083] 10. After the second annealing, turn off the heating power. Under continuous argon protection, slowly cool the furnace to 100°C at a set rate of 2°C / min. This process can fix the formed vacancy gradient structure. Then open the furnace door to allow it to cool rapidly to room temperature, thus obtaining CdS nanosheet material gradient-V with gradient concentration of Cd vacancies. Cd / CdS.

[0084] Example 3

[0085] A gradient-V method for constructing an ordered bulk phase polarization electric field induced by gradient concentration vacancies Cd / CdS photocatalyst preparation method:

[0086] 1. Dissolve 4 mmol of Cd(CH3COO)2·2H2O and 4 mmol of CS(NH2)2 in 40 mL of deionized water respectively;

[0087] 2. Mix the two solutions and add NH3·H2O dropwise under magnetic stirring to adjust the pH of the solution to 10;

[0088] 3. Transfer the mixed solution to a 100 mL polytetrafluoroethylene-lined high-pressure reactor, seal it, and place the reactor in an oven to react at a constant temperature of 160℃ for 15 h.

[0089] 4. After the reaction is complete, the mixture is allowed to cool naturally to room temperature. It is then washed three times with deionized water and ethanol, centrifuged to collect the yellow precipitate, and dried in a vacuum drying oven at 60℃ for 6 h to obtain the stoichiometric CdS nanosheet precursor.

[0090] 5. Weigh about 100 mg of the above CdS precursor powder and spread it evenly in a quartz boat. Place the quartz boat in the main heating zone (zone I) of the tube furnace. Place another quartz boat containing high-purity sulfur powder in another zone (zone II) upstream of the gas flow as a sulfur vapor source.

[0091] 6. Seal the quartz tube, open the inlet and outlet valves, and introduce high-purity Ar gas at a flow rate of 100 sccm for 30 minutes to remove air from the tube.

[0092] 7. The sulfur source temperature zone (temperature zone II) is heated to 150℃ to generate stable sulfur vapor. The S vapor atmosphere inhibits the formation of S vacancies and promotes the escape of Cd atoms from the crystal lattice at high temperature, thereby forming Cd vacancies. Simultaneously, the main temperature zone (temperature zone I) is programmed to rise to 480℃ at a rate of 5℃ / min, and isothermal annealed for 60 min in this sulfur vapor / argon mixed atmosphere; (During this stage, S atoms diffuse into the interior of the CdS crystal, while Cd atoms escape from the crystal lattice, forming Cd vacancies (VCd); this step aims to generate a high concentration of Cd vacancies on the sample surface layer.)

[0093] 8. After the first annealing is completed, turn off the heating of the sulfur source temperature zone and maintain the argon flow rate to purge the reaction tube for 10 minutes to completely remove the residual sulfur vapor in the tube;

[0094] 9. Under a pure argon atmosphere, maintain the temperature of the main temperature zone of the sample at 480℃ and continue isothermal annealing for 60 min (during this stage, the Cd vacancies enriched on the surface diffuse into the bulk phase of the material under the drive of the concentration gradient, thus forming a vacancy distribution gradient with decreasing concentration from the surface to the interior).

[0095] 10. After the second annealing, turn off the heating power. Under continuous argon protection, slowly cool the furnace body to 200°C at a set rate of 2°C / min. This process can fix the formed vacancy gradient structure. Then, open the furnace door to allow it to cool rapidly to room temperature, thus obtaining CdS nanosheet material gradient-V with gradient concentration of Cd vacancies. Cd / CdS.

[0096] Example 4

[0097] A gradient-V method for constructing an ordered bulk phase polarization electric field induced by gradient concentration vacancies Cd / CdS photocatalyst preparation method:

[0098] 1. Dissolve 4 mmol of Cd(CH3COO)2·2H2O and 4 mmol of CS(NH2)2 in 40 mL of deionized water respectively;

[0099] 2. Mix the two solutions and add NH3·H2O dropwise under magnetic stirring to adjust the pH of the solution to 10;

[0100] 3. Transfer the mixed solution to a 100 mL polytetrafluoroethylene-lined high-pressure reactor, seal it, and place the reactor in an oven to react at a constant temperature of 180°C for 12 h.

[0101] 4. After the reaction is complete, the mixture is allowed to cool naturally to room temperature. It is then washed once with deionized water and ethanol alternately. The yellow precipitate is collected by centrifugation and dried in a vacuum drying oven at 60℃ for 6 h to obtain the stoichiometric CdS nanosheet precursor.

[0102] 5. Weigh about 100 mg of the above CdS precursor powder and spread it evenly in a quartz boat. Place the quartz boat in the main heating zone (zone I) of the tube furnace. Place another quartz boat containing high-purity sulfur powder in another zone (zone II) upstream of the gas flow as a sulfur vapor source.

[0103] 6. Seal the quartz tube, open the inlet and outlet valves, and introduce high-purity Ar gas at a flow rate of 150 sccm for 60 minutes to remove air from the tube.

[0104] 7. Heat the sulfur source temperature zone (temperature zone II) to 150°C to generate stable sulfur vapor. At the same time, increase the temperature of the main temperature zone (temperature zone I) to 480°C at a rate of 5°C / min, and anneal at a constant temperature for 120 min in the sulfur vapor / argon mixed atmosphere.

[0105] 8. After the first annealing is completed, turn off the heating of the sulfur source temperature zone and maintain the argon flow rate to purge the reaction tube for 10 minutes to completely remove the residual sulfur vapor in the tube;

[0106] 9. Under a pure argon atmosphere, maintain the temperature of the main temperature zone of the sample at 480℃ and continue isothermal annealing for 90 min;

[0107] 10. After the second annealing, turn off the heating power. Under continuous argon protection, slowly cool the furnace to 200°C at a set rate of 2°C / min. This process can fix the formed vacancy gradient structure. Then open the furnace door to allow it to cool rapidly to room temperature, thus obtaining CdS nanosheet material gradient-V with a gradient concentration of Cd vacancies. Cd / CdS.

[0108] Example 5

[0109] A gradient-V method for constructing an ordered bulk phase polarization electric field induced by gradient concentration vacancies Cd / CdS photocatalyst preparation method:

[0110] 1. Dissolve 6 mmol of Cd(CH3COO)2·2H2O and 6 mmol of CS(NH2)2 in 60 mL of deionized water respectively;

[0111] 2. Mix the two solutions, and add NH3·H2O dropwise under magnetic stirring to adjust the pH of the solution to 11;

[0112] 3. Transfer the mixed solution to a 100 mL polytetrafluoroethylene-lined high-pressure reactor, seal it, and place the reactor in an oven to react at a constant temperature of 180°C for 18 h.

[0113] 4. After the reaction is complete, the mixture is allowed to cool naturally to room temperature. It is then washed 5 times with deionized water and ethanol alternately. The yellow precipitate is collected by centrifugation and dried in a vacuum drying oven at 80℃ for 10 h to obtain the stoichiometric CdS nanosheet precursor.

[0114] 5. Weigh about 150 mg of the above CdS precursor powder and spread it evenly in a quartz boat. Place the quartz boat in the main heating zone (zone I) of the tube furnace. Place another quartz boat containing high-purity sulfur powder in another zone (zone II) upstream of the gas flow as a sulfur vapor source.

[0115] 6. Seal the quartz tube, open the inlet and outlet valves, and introduce high-purity Ar gas at a flow rate of 150 sccm for 60 minutes to remove air from the tube.

[0116] 7. Heat the sulfur source temperature zone (temperature zone II) to 300℃ to generate stable sulfur vapor. At the same time, program the temperature of the main temperature zone (temperature zone I) to 600℃ at a rate of 8℃ / min, and anneal it at a constant temperature for 120 min in the sulfur vapor / argon mixed atmosphere.

[0117] 8. After the first annealing is completed, turn off the heating of the sulfur source temperature zone and maintain the argon flow rate to purge the reaction tube for 30 minutes to completely remove the residual sulfur vapor in the tube;

[0118] 9. Under a pure argon atmosphere, maintain the temperature of the main temperature zone of the sample at 600℃ and continue isothermal annealing for 90 min;

[0119] 10. After the second annealing, turn off the heating power. Under continuous argon protection, slowly cool the furnace to 300°C at a set rate of 5°C / min. This process fixes the formed vacancy gradient structure. Then open the furnace door to allow it to cool rapidly to room temperature, thus obtaining CdS nanosheet material gradient-V with a gradient concentration of Cd vacancies. Cd / CdS.

[0120] Test case

[0121] The composite photocatalysts from Examples 1-5 were used to conduct photocatalytic water splitting for hydrogen production experiments. The reaction conditions were as follows: a Pofil LABSOLAR-6A photocatalyst integrated testing device was used, comprising a light source, reaction equipment, a magnetically controlled gas circulation device, a vacuum device, a data acquisition device, and a chromatographic testing device. The photocatalytic water splitting hydrogen production system was connected to a gas chromatograph (GC), and the generated gas was injected into the GC for analysis. The GC was equipped with a thermal conductivity detector (TCD), using a 5A molecular sieve as the column and high-purity N2 as the carrier gas. The experimental parameters were set as follows: TCD device set to 150℃, vaporization chamber set to 110℃, and column set to 50℃. The specific operation of the photocatalytic hydrogen evolution experiment was as follows: 50 mg of photocatalyst was fully dispersed in a quartz reaction apparatus containing 10 mL of lactic acid and 90 mL of deionized water. The lactic acid served to consume holes. A 300 W xenon lamp was used as the simulated light source, and an optical filter (λ>420 nm, AM=1.5) was used to filter the ultraviolet light. The hydrogen production rate was detected using gas chromatography. Before illumination, the entire system (including the solution) was degassed with high-purity N2 to remove O2 from the apparatus. The temperature of the reaction system was maintained at 10 ± 0.5 °C using a constant-temperature water bath. The hydrogen production test results are shown in Table 1, indicating that the hydrogen production rate of the photocatalyst in this system reached 400 mmol / h. -1 g -1 .

[0122] Table 1. Comparison of hydrogen production rates from photocatalytic water splitting

[0123] <![CDATA[hydrogen production rate (mmol h -1 g -1 )]]> Hydrogen production stability (h) Example 1 280 ≥24 Example 2 350 ≥24 Example 3 400 ≥24 Example 4 360 ≥24 Example 5 300 ≥24

[0124] Comparison Example

[0125] To compare the photocatalytic performance of this system in water splitting for hydrogen production, the hydrogen production rates of the CdS composite photocatalysts are listed below. Patent CN112808280A discloses an S-doped TiO2-CdS composite photocatalytic hydrogen production material, which achieves an optimal hydrogen production rate of approximately 1.31 mmol / h under 300W xenon lamp illumination. -1 g -1 Patent CN112121834A discloses an MXene / CdS composite photocatalyst with an optimal hydrogen production rate of approximately 3.71 mmol / h. -1 g -1 Patent CN113398998A discloses a Zr-MOF@CdS photocatalyst with an optimal hydrogen production rate averaging approximately 1.86 mmol / h. -1 g -1 Patent CN103381367A discloses a CdS / Ba 0.9 Zn 0.1The optimal hydrogen production rate of the TiO3 composite photocatalyst is approximately 1.47 mmol / h. -1 g -1 Patent CN116809090A discloses a 2D / 1D Ni2P / CdS heterojunction catalyst with a hydrogen production rate of 4.3 mmol / h / g. Patent CN115445637B discloses a Cd / CdS heterojunction with a hydrogen production efficiency of 10.6 mmol / h / g. Patent CN119140123A discloses a MoS2 / CdS heterojunction composite photocatalyst with a hydrogen production rate of 9.7 mmol / h / g. Patent CN121130914A discloses a NiO-NiS / CdS ternary composite heterojunction photocatalyst with a hydrogen production rate of 32 mmol / h / g. Therefore, the photocatalyst synthesized in this invention exhibits significantly higher photocatalytic water splitting and hydrogen production performance.

[0126] Figure 2 For gradient-V Cd The XRD spectrum of / CdS corresponds to the standard spectrum of hexagonal CdS, and the crystal form does not change after the introduction of vacancies.

[0127] Figure 3 For CdS and gradient-V Cd The SEM images of / CdS all show relatively thin nanosheet morphologies. The two-dimensional thin sheet structure has a high specific surface area, which is conducive to the full interaction between the atmosphere and the surface. Moreover, the short diffusion path is conducive to the efficient formation and control of the gradient. The morphology did not change significantly after the introduction of vacancies.

[0128] Figure 4 For CdS and gradient-V Cd The UV-Vis absorption spectrum of CdS, gradient-V Cd The spectral response range and light absorption intensity of / CdS are significantly improved, indicating that the present invention effectively solves the problem of defects affecting light absorption.

[0129] Figure 5 For CdS and gradient-V Cd Time-resolved fluorescence spectrum of CdS, gradient-V Cd The significantly improved photogenerated carrier lifetime of / CdS indicates that the polarized electric field formed by this system effectively promotes the separation and transport of bulk electrons and holes.

[0130] Figure 6 CdS, surface disorder V Cd / CdS and gradient-V Cd Comparison of hydrogen production performance of / CdS, gradient-V CdThe hydrogen production of CdS reached 400 mmol / h / g, which is much higher than that of CdS and surface disordered V. Cd The hydrogen production rate of / CdS indicates that the gradient vacancy-induced bulk phase ordered polarization electric field design can significantly improve the photocatalytic performance of CdS.

[0131] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing cadmium sulfide photocatalysts based on gradient concentration cadmium vacancy-induced ordered bulk polarized electric fields, characterized in that the method... include: (1) Cadmium sulfide nanosheet precursor was prepared by hydrothermal method under alkaline conditions from a mixture of cadmium source and sulfur source; (2) The cadmium sulfide nanosheet precursor is heat-treated in a sulfur-containing inert gas atmosphere and then subjected to a first isothermal annealing to generate a high concentration of Cd vacancies on the surface layer of the cadmium sulfide nanosheet. (3) The product obtained after step (2) is subjected to a second isothermal annealing in an inert gas atmosphere, and the annealing temperature is the same as the temperature of the first isothermal annealing. (4) Under an inert gas atmosphere, the product after step (3) is subjected to a two-stage cooling process to obtain cadmium sulfide nanosheet material with gradient concentration of Cd vacancies.

2. The method for preparing cadmium sulfide photocatalyst based on gradient concentration cadmium vacancy-induced ordered bulk polarized electric field according to claim 1, characterized in that, In step (1), the preparation of cadmium sulfide nanosheet precursors from a mixture of cadmium and sulfur sources under alkaline conditions via a hydrothermal method includes: The cadmium source and sulfur source were dissolved separately in deionized water to prepare solutions. The two solutions were then mixed, and an alkaline reagent was added under stirring to adjust the pH of the solution to 9-11, thus forming a mixed solution. The mixed solution was transferred to a high-pressure reactor and sealed, and reacted at a constant temperature of 120–180°C for 10–20 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The precipitate was then washed, centrifuged, and collected. It was then vacuum dried at 50–80 °C for 2–10 h to obtain the cadmium sulfide nanosheet precursor.

3. The method for preparing cadmium sulfide photocatalyst based on gradient concentration cadmium vacancy-induced ordered bulk polarized electric field according to claim 1, characterized in that, In step (2), the heating rate of the heat treatment is 2 to 8 °C / min.

4. The method for preparing cadmium sulfide photocatalyst based on gradient concentration cadmium vacancy-induced ordered bulk polarized electric field according to claim 1, characterized in that, In step (2), the temperature of the first isothermal annealing is 300-600℃, and the annealing time is 30-120 min.

5. The method for preparing cadmium sulfide photocatalyst based on gradient concentration cadmium vacancy-induced ordered bulk polarized electric field according to claim 1, characterized in that, In step (3), the temperature of the second isothermal annealing is 300-600℃, and the annealing time is 30-90 min.

6. The method for preparing cadmium sulfide photocatalyst based on gradient concentration cadmium vacancy-induced ordered bulk polarized electric field according to claim 1, characterized in that, In step (4), the two-stage cooling process includes: First, a slow cooling process controlled by a program is performed to lower the temperature to 100-300℃, and then a second rapid cooling process is performed to lower the temperature to room temperature. The cooling rate of the first stage of slow cooling is 1–5 °C / min.

7. The method for preparing cadmium sulfide photocatalyst based on gradient concentration cadmium vacancy-induced ordered bulk polarized electric field according to claim 1 or 2, characterized in that, The cadmium source is one of cadmium acetate, cadmium nitrate, cadmium chloride, cadmium perchlorate, cadmium carbonate, cadmium chloride, cadmium bromide, and cadmium iodide; and the sulfur source is one of thiourea, sodium sulfide, thioacetamide, sodium thiosulfate, ammonium sulfide, and ammonium thiosulfate. The alkaline reagent is one of ammonia, ethylenediamine, ethanolamine, triethanolamine, sodium hydroxide, and potassium hydroxide.

8. A cadmium sulfide photocatalyst based on an ordered bulk polarized electric field induced by gradient concentration cadmium vacancies, characterized in that, Prepared by the method according to any one of claims 1 to 7, the concentration of Cd vacancies in the cadmium sulfide catalyst exhibits a gradient distribution that decreases from the surface to the interior.

9. Application of cadmium sulfide photocatalyst based on gradient concentration cadmium vacancy-induced ordered bulk phase polarized electric field in photocatalytic water splitting for hydrogen production.

Citation Information

Patent Citations

  • Photocatalytic water splitting hydrogen production material CdS / Ba0.9Zn0.1TiO3 and preparation method thereof

    CN103381367A

  • MXene / CdS composite photocatalyst as well as preparation method and application thereof in hydrogen production by water splitting

    CN112121834A

  • S-doped TiO2-CdS composite photocatalytic hydrogen production material and preparation method thereof

    CN112808280A

  • Zr-MOF@CdS photocatalyst and preparation method thereof, and application of Zr-MOF@CdS photocatalyst in hydrogen production through photocatalytic water decomposition

    CN113398998A

  • A cadmium / cadmium sulfide heterojunction and its preparation method and application in visible light photocatalytic decomposition of water to produce hydrogen

    CN115445637B